ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENUNJUKAN KANTOR AKUNTAN PUBLIK SEBAGAI AUDITOR EKSTERNAL - Basyiruddin Nur; Muhammad Nur Yahya (Jurnal Telaah dan Riset Akuntansi, 2011)
The purpose of this research is to study the influence of several factors namely, reputation, competence, independency, fee, duration of audit and related regulations to the appointment of Public Accounting Firm as external auditor to execute general audit to the financial statements.This research used simple random sampling technique of survey by questionnaires whose respondents were the companies demanding general audit services provided by Public Accounting Firm.The result of this research indicates that several factors influence the decision of appointment of Public Accounting Firm as external auditor as follow : (1) independency of Public Accounting Firm. (2)audit fee (3) duration of fieldwork and submission of final audit report. (4) related regulation either upon to Public Accounting Firm or to it’s client. While on the other hand the reputation and competence factors do not influence to appointment of Public Accounting Firm as external auditor. Keywords : Public Accounting Firm, reputation, competence, independence, fee, duration of audit, regulations.